Integrating Philosophy of Science into Islamic Education: Enhancing Relevance and Effectiveness in the Fourth Industrial Revolution Era - Dian Dian; Syafira Fadilah; Nenden Ahadiah Halimah; Oop Sopiyulloh (STAI Hubbulwathan Duri, 2025)
The Industrial Revolution 4.0 has created unprecedented challenges and opportunities for educational systems, including Islamic education. In this context, re-evaluating foundational frameworks becomes crucial. This study explores the role of the philosophy of science in enhancing the effectiveness of Islamic education management amidst technological transformation. A qualitative-descriptive approach was employed using literature research. The study analyzed existing scholarly works on the philosophy of science, Islamic education management, and the implications of the Industrial Revolution 4.0. The findings reveal that the philosophy of science serves as a rational epistemological foundation for modernizing Islamic education. It supports adaptive curriculum development, facilitates the integration of Islamic values with technological advancements, and promotes hybrid learning models that blend traditional pedagogy with digital tools. These elements contribute to institutional effectiveness in the digital era. Applying the philosophy of science in Islamic education management enables strategic decision-making, leadership development, and technology integration aligned with Islamic pedagogical principles. It acts as an intellectual compass guiding Islamic education toward societal welfare and sustainable progress.